How Long Is a Week? - Claire Clark (Bharat Capstone Press, 2012)
A lot happens in a week! It's one whole row on the calendar. In one week you might take a trip or have a celebration. You might learn something new! Find out more in How Long Is a Week?
Keywords: Non Fiction -- Non Fiction